Histological typing of ovarian tumours - Scully, Robert E; Sobin, L. H (Springer, 1999)
The second edition of this book presents an internationally approved classification of ovarian tumours, including a number of entities that were not included in the previous edition, such as transitional cell carcinoma, small cell carcinoma, hepatoid carcinoma, hepatoid and glandular yolk sac tumours, and retiform Sertoli-Leydig cell tumour. Also included in the volume is the TNM staging system for ovarian tumours with illustrations.
International histological classification of tumours, ISSN 0538-7736
Keywords: histologie; patologie; Ovarian Neoplasms; nádory vaječníků; onkologie; gynekologie a porodnictví